Correction: Stimuli responsive nanostructured porous network from triblock copolymer self-assemblies. Issue 25 (8th June 2015) - Mouline, Zineb; Semsarilar, Mona; Barboiu, Mihail; Deratani, Andre; Quemener, Damien
Abstract : Correction for 'Stimuli responsive nanostructured porous network from triblock copolymer self-assemblies' by Zineb Mouline, et al., Polym. Chem., 2015, 6, 2023–2028.